EFFECT OF RANIBIZUMAB ON HIGH-SPEED INDOCYANINE GREEN ANGIOGRAPHY AND MINIMUM INTENSITY PROJECTION OPTICAL COHERENCE TOMOGRAPHY FINDINGS IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 1 (January 2015) - Nicholson, Benjamin P.; Nigam, Divya; Toy, Brian; Stetson, Paul F.; Agrón, Elvira; Jacobs-El, Naima; Cunningham, Denise; Cukras, Catherine; Wong, Wai; Wiley, Henry; Chew, Emily; Ferris, Frederick; et al.
Abstract : Purpose: The purpose of this 1-year prospective study was to investigate how induction/pro re nata ranibizumab intravitreal treatment of eyes with neovascular age-related macular degeneration affects the anatomy of choroidal neovascularization (CNV) and the overlying outer retinal tissue. Methods: High-speed indocyanine green (HS-ICG) angiography measurements provided quantification of the CNV size in 60 patients followed for 1 year. Minimum intensity projection optical coherence tomography (MinIP OCT), a novel algorithm assessing minimum optical intensity between the internal limiting membrane and retinal pigment epithelium, measured the area of outer retinal disruption overlying the CNV. Fluorescein angiography was also assessed to evaluate late retinal leakage. Results: After 1 year, the mean area of CNV measured with indocyanine green angiography decreased by 5.8%. The mean area of MinIP OCT of outer retinal disruption overlying the CNV decreased by 4.2%. Mean area of fluorescein angiography leakage decreased by 6.3%. Both the area of outer retinal disruption measured with MinIP OCT and the area of leakage on fluorescein angiography typically exceeded the area of CNV on indocyanine green angiography at baseline and 1 year. Conclusion: Choroidal neovascularization treated with induction/pro re nata intravitreal ranibizumab for 1 year essentially remained static. Minimum intensity projection optical coherence tomography suggests that the area of outer retinal disruption overlying the CNV may be greater than the CNV itself and often correlates with the leakage area on fluorescein angiography. Additionally, there was minimal change in the area of outer retinal disruption on MinIP OCT even when fluid resolved. Measurements of the extent of CNV lesions based on indocyanine green angiography and MinIP OCT may provide useful outcome variables to help assess the CNV complex longitudinally and warrant further validation. Abstract : Choroidal neovascularization, assessed quantitatively with high-speed indocyanine green angiography, and the overlying outer retinal tissue alterations, measured with minimum intensity projection optical coherence tomography, remain essentially static during 1 year of treatment with induction/pro re nata intravitreal ranibizumab for neovascular age-related macular degeneration.